Prospective assessment of NGS-detectable mutations in CML patients with nonoptimal response: the NEXT-in-CML study - Soverini, Simona; Bavaro, Luana; De Benedittis, Caterina; Martelli, Margherita; Iurlo, Alessandra; Orofino, Nicola; Sica, Simona; Sorà, Federica; Lunghi, Francesca; Ciceri, Fabio; Galimberti, Sara; Baratè, Claudia; et al. (Blood, 2020)
In chronic myeloid leukemia (CML) patients, tyrosine kinase inhibitors (TKIs) may select for drug-resistant BCR-ABL1 kinase domain (KD) mutants. Although Sanger sequencing (SS) is considered the gold standard for BCR-ABL1 KD mutation screening, next-generation sequencing (NGS) has recently been assessed in retrospective studies. We conducted a prospective, multicenter study (NEXT-in-CML) to assess the frequency and clinical relevance of low-level mutations and the feasibility, cost, and turnaround times of NGS-based BCR-ABL1 mutation screening in a routine setting. A series of 236 consecutive CML patients with failure (n = 124) or warning (n = 112) response to TKI therapy were analyzed in parallel by SS and NGS in 1 of 4 reference laboratories. Fifty-one patients (22 failure, 29 warning) who were negative for mutations by SS had low-level mutations detectable by NGS. Moreover, 29 (27 failure, 2 warning) of 60 patients who were positive for mutations by SS showed additional low-level mutations. Thus, mutations undetectable by SS were identified in 80 out of 236 patients (34%), of whom 42 (18% of the total) had low-level mutations somehow relevant for clinical decision making. Prospective monitoring of mutation kinetics demonstrated that TKI-resistant low-level mutations are invariably selected if the patients are not switched to another TKI or if they are switched to a inappropriate TKI or TKI dose. The NEXT-in-CML study provides for the first time robust demonstration of the clinical relevance of low-level mutations, supporting the incorporation of NGS-based BCR-ABL1 KD mutation screening results in the clinical decision algorithms. •NGS provides a more accurate picture of BCR-ABL1 mutation status in CML patients with failure or warning responses to TKI therapy.•TKI-resistant low-level mutations undergo selective expansion if the TKI is not changed or an inappropriate TKI or TKI dose is chosen. [Display omitted]